Isomorphic Circuits of Independent Amplitude Tunable Voltage-Mode Bandpass Filters and Quadrature Sinusoidal Oscillators - San-Fu Wang (Applied Sciences, 2021)
This paper presents isomorphic circuits of voltage-mode (VM) non-inverting bandpass filters (NBPFs) and VM quadrature sinusoidal oscillators (QSOs) with independent amplitude control functionality. The proposed VM NBPFs and VM QSOs exhibit low-output impedance and independent amplitude control, which are important for easily cascading the VM operation and independent control of the amplitude gain. The proposed isomorphic circuits employ three LT1228 commercial integrated circuits (ICs), two grounded capacitors, two grounded resistors and one floating resistor. The use of grounded capacitors is beneficial for the implementation of the IC. Both NBPFs have a high-input impedance and have a wide range of independent amplitude tunable passband gain without affecting the quality factor (Q) and center frequency (fo). The Q and fo parameters of the proposed NBPFs are orthogonal tunability. By feeding back each input signal to the output response of the NBPF, two VM fully uncoupled QSOs are also proposed. The proposed VM fully uncoupled QSOs have two quadrature sinusoidal waveforms with two low-output impedances and one independent amplitude tunable sinusoidal waveform. The frequency of oscillation (FO) and the condition of oscillation (CO) are fully uncoupled and controlled electronically. The performances of the proposed isomorphic circuits have been tested with a ±5 volt power supply and are demonstrated by experimental measurements which confirm the theoretical assumptions.